The effect of transcranial Direct Current Stimulation on the Iowa Gambling Task: a scoping review - Salice, Silvia; Antonietti, Alessandro; Colautti, Laura (Frontiers in Psychology, 2024)
Introduction Among the tasks employed to investigate decisional processes, the Iowa Gambling Task (IGT) appears to be the most effective since it allows for deepening the progressive learning process based on feedback on previous choices. Recently, the study of decision making through the IGT has been combined with the application of transcranial direct current stimulation (tDCS) to understand the cognitive mechanisms and the neural structures involved. However, to date no review regarding the effects of tDCS on decisional processes assessed through the IGT is available. This scoping review aims to provide a comprehensive exploration of the potential effects of tDCS in enhancing decisional processes, assessed with the IGT, through the evaluation of the complete range of target cases. Methods The existing literature was analyzed through the PRISMA approach. Results Results reported that tDCS can enhance performance in the IGT and highlighted a pivotal role of the dorsolateral prefrontal cortex and the orbitofrontal cortex in risky and ambiguous decisions. Discussion Thus, tDCS over the brain regions identified improves the decisional processes in healthy subjects and patients, confirming its potential to enhance decision making in everyday contexts and deepen the neural correlates. Suggestions for further studies are provided to delve into decisional mechanisms and how to better support them.